The role of intellectual disability with autism spectrum disorder and the documented cooccurring conditions: A population‐based study. Issue 12 (17th October 2022) - Etyemez, Semra; Esler, Amy; Kini, Aniket; Tsai, Peng‐Chou; DiRienzo, Monica; Maenner, Matthew; Lee, Li‐Ching
Abstract: Previous research has identified that patterns of cooccurring conditions (CoCs) associated with autism spectrum disorder (ASD) differ based on the presence of intellectual disability (ID). This study explored the association of documented CoCs among 8‐year‐old children with ASD and ID (ASD+ID, n  = 2416) and ASD without ID (ASD‐ID, n  = 5372) identified by the Autism and Developmental Disabilities Monitoring Network, surveillance years (SYs) 2012 and 2014. After adjusting for demographic variables, record source, surveillance site, and SY, children with ASD+ID, as compared with children with ASD‐ID, were more likely to have histories of nonspecific developmental delays and neurological disorders documented in their records but were less likely to have behavioral and psychiatric disorders. ID plays a key role on how children with ASD would experience other CoCs. Our results emphasize how understanding the pattern of CoCs in ASD+ID and ASD‐ID can inform comprehensive and multidisciplinary approaches in assessment and management of children in order to develop targeted interventions to reduce possible CoCs or CoCs‐related impairments. Lay Summary: CoCs are common among children with either ASD or ID which can complicate diagnosis and treatment decisions. We compared these CoCs in children with ASD and ID and children with ASD without ID. Our results suggest that children with ASD and ID are more likely to have histories of nonspecific developmental delays and neurological disorders but were less likely to have behavioral and psychiatric conditions compared with children with ASD but not ID.